2015
DOI: 10.1007/s11948-015-9678-5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Ethics Training on International and US Students

Abstract: As scientific and engineering efforts become increasingly global in nature, the need to understand differences in perceptions of research ethics issues across countries and cultures is imperative. However, investigations into the connection between nationality and ethical decision-making in the sciences have largely generated mixed results. In Study 1 of this paper, a measure of biases and compensatory strategies that could influence ethical decisions was administered. Results from this study indicated that gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 69 publications
0
4
0
3
Order By: Relevance
“…Ludlum and Sergey (2005) however suggests that training can also help to encourage students to act more ethically. Similarly Steele et al (2016) demonstrated a generally positive linkage between ethics training and ethical decision making of students. While the present study does not concern itself with the relationship between ethics training and ethics conduct, it considers that the awareness of unethical behaviour by students is an important step in influencing their ethical conduct.…”
Section: Role Of Education In Shaping Ethical Behaviourmentioning
confidence: 95%
“…Ludlum and Sergey (2005) however suggests that training can also help to encourage students to act more ethically. Similarly Steele et al (2016) demonstrated a generally positive linkage between ethics training and ethical decision making of students. While the present study does not concern itself with the relationship between ethics training and ethics conduct, it considers that the awareness of unethical behaviour by students is an important step in influencing their ethical conduct.…”
Section: Role Of Education In Shaping Ethical Behaviourmentioning
confidence: 95%
“…In the workplace setting, culture influences people’s views, practices, and interactions, such as their approaches to teamwork, strategies for negotiation, and attitudes to leadership (Dickson et al 2003; Gelfand et al 2013; Ralston et al 1997; Ramesh and Gelfand 2010; Aycan and Gelfand 2012). However, only recently have members of the scientific community begun to consider the role of culture in the work of researchers and in research integrity (Heitman 2014; Hwang 2013; InterAcademy Parternership 2016; Steele, Johnson, Watts, MacDougall, Mumford, Connelly, & Williams, 2016; Nho 2016; Steneck 2013). Scholars have considered the need for cultural sensitivity with regard to culturally diverse research participants (Benatar 2000; Calamaro 2008; Marshall 2008), but generally have not examined such issues among culturally diverse researchers working together.…”
Section: Introductionmentioning
confidence: 99%
“…Bu nedenle müfredatta yer alan etik öğretiminin tamamen mühendislik odaklı olması gerekmediği, öğrencilerin mümkün olduğunca etik profesyonel mühendislik rol modellerine maruz bırakılması gerektiği ve bunun biçimsel ders veya özel ders şeklinde olabileceği, ancak mühendislik danışmanlığı ve etik davranışların akademik mühendislik personeli tarafından modellenmesi şeklinde olduğunda çok daha faydalı olabileceği belirtilmiştir [8]. Bununla birlikte etik ve ahlaki gelişim üzerine yapılan bazı çalışmalar, profesyonel mühendislik etiği eğitiminin öğrencilerin etik davranma eğilimini güçlendirdiğini ortaya koymuştur [10][11][12].…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Steele vd. [12], ABD'deki lisansüstü öğrencilerin ve ABD'de okuyan uluslararası öğrencilerin etik algılarını karşılaştırmış ve öğrencilerin uyruğunun öğrencilerin etik algıları üzerinde önemli bir etkisi olduğu sonucuna varmıştır. İki grupla yapılan bir odak grup çalışması etik eğitimine katılan bir grup ile katılmayan bir grup arasında etik karar verme konusunda önemli bir farklılık olmadığını ortaya koymuştur.…”
Section: Gi̇ri̇ş (Introduction)unclassified
See 1 more Smart Citation